Time allocation between work and family over the life-cycle: a comparative gender analysis of Italy, France, Sweden and the United States - Dominique Anxo (Institute for the Study of Labor (IZA), 2007)
This article analyses the extent to which changes in household composition over the life course affect the gender division of labour. It identifies and analyses cross-country disparities between France, Italy, Sweden and United States, using most recent data available from the Time Use National Surveys. We focus on gender differences in the allocation of time between market work, domestic work and leisure over the life-cycle. In order to map the life-cycle, we distinguish between nine key cross-country comparable life stages according to age and family structure such as exiting parental home, union formation, parenthood, and retiring from work. By using appropriate regression techniques (Tobit with selection, Tobit and OLS), we show large discrepancies in the gender division of labour at the different life stages. This gender gap exists in all countries at any stage of the life course, but is usually smaller at the two ends of the age distribution, and larger with parenthood. Beyond social norms, the impact of parenthood on time allocation varies across countries, being smaller in those where work-family balance policies are more effective and traditionally well-established.
Keywords: D13; 330; Time use; gender; life-cycle; paid and unpaid work; Familienökonomik; Arbeitsangebot; Hausarbeit; Lebenszyklus; Geschlecht; Frauenerwerbstätigkeit; Vergleich; Frankreich; Italien; Schweden; USA